Role of Regulatory Authorities on the Working of Contract Research Organization and Pharmaceutical Company's Clinical Trials in India - Poonam Chauhan; Monica Mendonica (ACHSM, 2021)
The evolution of the drug development process and testing its efficacy is a primary responsibility of pharmaceutical companies. The time cost investment involved in identifying a compound suitable to its target disease and making it available to the masses eventually led to the rise of the Contract Research Organization (CRO) in the domain of clinical research.  Pharmaceutical companies outsource the research and clinical trials to CRO's. A CRO has a vital role from drug discovery to the launch and marketing of drugs. India is emerging as attractive location for global clinical trial. It has cost advantage compared to other countries and a well-developed associated services like data management, medical writing and pharmacovigilance.  The Central Drug Standard Control Organization (CDSCO) is the National Regulatory Authority in India that aims to bring safe drugs and standardize clinical research. Pharmaceutical Companies benefit by strategically working with CRO to gain speed and efficiency in drug discovery, generation and retention of clinical data integrity. The risk associated with CRO relates to delays and inferior quality of work, thereby making CRO a critical decision for Pharmaceutical Company.